Dispute over the Calculation of the Number of Votes in the Election of the Head of Huraba Village 1, Siabu District, Mandailing Natal Regency, Fiqh Siyasah Perspective (Analysis Study of Decision Number: 68/G/2023/Ptun.Mdn) - Agus Wibowo; Annisa Sativa (Warmadewa Press, 2024)
This study aims to analyze the PTUN Decision Number: 68/G/2023/PTUN.MDN regarding the vote counting dispute in the Huraba 1 village head election from the perspective of Fiqh Siyasah. The main objectives of this research are to, Identify and evaluate inconsistencies in the vote counting process that formed the basis of the dispute. Analyze the court decision in the context of justice and legal certainty principles (Al-Adl and Al-Yaqin) according to Fiqh Siyasah. Assess whether the court's decision aligns with the principles of Fiqh Siyasah and provide recommendations for improving the election process. Through this approach, the study aims to offer a deeper understanding of legal applications in election disputes and the relevance of Fiqh Siyasah principles in ensuring justice and legal certainty. The research results show that the Medan PTUN rejected the lawsuit from the plaintiff because it was deemed to violate the principles of good government. From the perspective of Fiqh Siyasah (Qadha'iyyah), this decision is in line with the principles of justice (al-'adl), legal certainty (al-yaqin), and benefit (maslahah) in Islamic government administration. This research concludes the importance of applying the principles of Fiqh Siyasah in administrative decision making to ensure justice and public benefit.